VERBAL ABUSE AND CHILDREN’S DEVELOPMENT IN LYAMUTUNDWE VILLAGE, WAKISO DISTRICT-UGANDA: AN EXPLORATORY STUDY. - Kusemererwa, Mary Sunday; Bukenya, Aloysius Lwanga (Student's Journal of Health Research Africa, 2024)
Background The community of Lyamutundwe village in Wakiso District, Uganda, engages in constant interactions between adults and children. There are abusive practices by child caretakers that go unreported and those include the use of child verbal abuse. Considering the education status of many residents of Lyamutundwe, one would assume that matters of safeguarding children from the effects of verbal abuse would be abated by highlighting their existence and addressing them. This, however, is not the case. This observation engendered a study that aimed at investigating the beliefs of caregivers about verbal abuse and how it affects children’s growth and development. The main questions were: What beliefs do caregivers hold as they interact with children? What caused adults to use abusive words to children? What could be done to abate the effects of child verbal abuse? Methodology The dominantly qualitative study, which was of exploratory study design, used the open-ended methods: oral interviews, participatory observations, and focus group discussions. These elicited data from the respondents that highlighted the beliefs about abusive words and perceptions of their impact on children’s self-esteem and development. Discussion The study discovered that depending on their beliefs about the impact of verbal abuse on children, caregivers behave differently. Those respondents who considered verbal abuse useful maintained its use while disciplining children; those who considered it destructive, because it humiliated and demoralized children, reported that they avoided it. Overall, it was observed that discouraging, blaming children, and making jokes about them were expressions of verbal abuse that negatively impacted children’s development. The study recommended that young parents in Lyamutundwe be inducted into parental roles and made aware of the dangers of child verbal abuse. The findings and recommendations could be generalized to young families in Wakiso District, and largely to Uganda and globally world over.